Building a Species Conservation Strategy for the Brown Howler Monkey (Alouatta Guariba Clamitans) in Argentina in the Context of Yellow Fever Outbreaks. (March 2014) - Agostini, Ilaria; Holzmann, Ingrid; Di Bitetti, Mario S.; Oklander, Luciana I.; Kowalewski, Martín M.; Beldomnico, Pablo M.; Goenaga, Silvina; Martínez, Mariela; Moreno, Eduardo S.; Lestani, Eduardo; Desbiez, Arnaud L. J.; Miller, Philip
The brown howler monkey ( Alouatta guariba clamitans ) is endemic to South America's Atlantic Forest, with a small population extending into the northern portion of Misiones province in northeastern Argentina. In 2012, the species was classified as Critically Endangered in Argentina due to its highly restricted distribution, low population density and dramatic declines from recent Yellow Fever outbreaks. In March 2013, we organized an international workshop in Misiones to evaluate population status in Argentina and conduct a threat analysis. We developed population viability models using Vortex and Outbreak software packages. These tools allowed us to explore how several biological and demographic parameters of brown howlers, as well as factors related to Yellow Fever epidemiology, affect the probability of species extinction. The discussion among diverse specialists and analysis of model results identified Yellow Fever as the main threat to brown howler population persistence in Argentina. Our threat analysis, focused on the dynamics of Yellow Fever outbreaks and their impact on howler populations, led to the identification of gaps in knowledge that helped prioritize objectives and actions for the development of a Species Conservation Strategy in Argentina.